Hall effect on thermal instability of viscoelastic dusty fluid in porous medium - Singh, Mahinder; Gupta, R.K. (Zielona Góra: Uniwersytet Zielonogórski)
The effect of Hall currents and suspended dusty particles on the hydromagnetic stability of a compressible, electrically conducting Rivlin-Ericksen elastico viscous fluid in a porous medium is considered. Following the linearized stability theory and normal mode analysis the dispersion relation is obtained. For the case of stationary convection, Hall currents and suspended particles are found to have destabilizing effects whereas compressibility and magnetic field have stabilizing effects on the system.
Keywords: thermal instability; Rivlin-Ericksen viscoelastic fluid; suspended particles; Hall current effect; porous medium